2013
DOI: 10.1186/scrt198
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of intravenous infusion of allogeneic cryopreserved mesenchymal stem cells for treatment of chronic kidney disease in cats: results of three sequential pilot studies

Abstract: IntroductionAdministration of mesenchymal stem cells (MSCs) has been shown to improve renal function in rodent models of chronic kidney disease (CKD), in part by reducing intrarenal inflammation and suppressing fibrosis. CKD in cats is characterized by tubulointerstitial inflammation and fibrosis, and thus treatment with MSCs might improve renal function and urinary markers of inflammation in this disease. Therefore, a series of pilot studies was conducted to assess the safety and efficacy of intravenous admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
124
0
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(144 citation statements)
references
References 40 publications
3
124
0
17
Order By: Relevance
“…However, in this study, no adverse effects were observed during or after MSC transplantation. Conversely, intravenous transplantation enables the activation of paracrine, anti-inflammatory, immunomodulatory, and anti-fibrotic mechanisms, which are important in stem cell-based therapies (Deak et al, 2010;Quimby et al, 2013). A high mortality rate was observed in both groups, which may be related to acute clinical and neurological symptoms and to the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, no adverse effects were observed during or after MSC transplantation. Conversely, intravenous transplantation enables the activation of paracrine, anti-inflammatory, immunomodulatory, and anti-fibrotic mechanisms, which are important in stem cell-based therapies (Deak et al, 2010;Quimby et al, 2013). A high mortality rate was observed in both groups, which may be related to acute clinical and neurological symptoms and to the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The cryoprotectant, DMSO, in VS55 cryopreservation medium is a known carcinogen that can cause serious side effects when administered intravenously at relatively low concentrations in cell suspensions (14,15). Removal can be complicated and time consuming (16).…”
mentioning
confidence: 99%
“…Possíveis mecanismos KIM et al, 2007;TOGEL et al, 2007;QUIMBY et al, 2011;QUIMBY et al, 2013;DOW, 2015).…”
Section: Discussionunclassified
“…Recentemente, diversos estudos tem sugerido o uso de célula-tronco mesenquimal como uma nova opção de tratamento na doença renal crônica, encourajado a partir de estudos realizado em ratos e camundongos, bem como na espécie felina e canina (CAVAGLIERI et al, 2009;SEMEDO et al, 2009;LEE et al, 2010;QUIMBY et al, 2011;VILLANUEVA et al, 2011;QUIMBY et al, 2013;DOW, 2015;LIM et al, 2016).…”
unclassified
See 1 more Smart Citation